1988
DOI: 10.1108/eb051694
|View full text |Cite
|
Sign up to set email alerts
|

Developing Managers for an International Business

Abstract: Management development practice within ICI is discussed. The proposition that a manager is only as good as the culture in which he works (its general standards, values, behaviours, control and rewards systems) is considered. The culture of an organisation can have both a positive and a negative effect on the performance of a manager and those responsible for management development activities must maintain a progressive cultural setting which allows people to flourish and display their talents. The purpose of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A growing number of researchers have agreed on the importance of certain competencies, which were also promoted by senior management firms as SHL [63], Schroder [64] and Vincent [65]. This indicates that it is possible to create a universal competency model for assessing managers.…”
Section: Brief Description and Measurability Of Management Competenciesmentioning
confidence: 99%
“…A growing number of researchers have agreed on the importance of certain competencies, which were also promoted by senior management firms as SHL [63], Schroder [64] and Vincent [65]. This indicates that it is possible to create a universal competency model for assessing managers.…”
Section: Brief Description and Measurability Of Management Competenciesmentioning
confidence: 99%
“…Many authors have subsequently explored the concept and two approaches appear to have found favour. The first approach placed emphasis on the behavioural aspect of a competency by defining it as a set of behaviour patterns that the incumbent needs to bring to a position in order to perform its tasks and functions with competence (Human & Human, 1989;Meyer, 1996;Schroder, 1989;Vincent, 1988;Woodruffe, 1993). Central to this view is the notion that a competency is a dimension of overt and manifest behaviour that allows a person to perform competently, incorporating both the desire and the ability to behave in a competent way.…”
Section: Bongani Mbokazi Deléne Visser Linda Fouriementioning
confidence: 99%
“…Corresponding with the overwhelming emphasis on the competency approach to management development and along with it, its increased acceptability, several taxonomies of managerial competence have been put forward (Analoui, 1995;Cockerill, Hunt & Schroder, 2000;Education Review Office, 1995;Katz, 1974;Mann & Staudenmier, 1991;Mintzberg, 1980;Peter, 1984;Profiles International, 2000;SHL, 1994;Williamson, 1981). These theories indicate a myriad of key competencies, which are briefly summarised in Table 1. Increasing consensus, backed by authorities such as SHL (1993), Schroder (1989) and Vincent (1988), has built up over the years suggesting that it is possible to create a universal or core competency model for the assessment of managers. Three broad domains of managerial competence appear to emerge: Firstly, the competency to manage the task; secondly, the competency to manage people and thirdly, the competency to manage the "self".…”
Section: Management Competenciesmentioning
confidence: 99%